A Comparative Study of the Reconciliation Efforts of the Thai and Indonesian Governments in Developing Islamic Education - Sutrisno, Sutrisno; Fakhruddin, Fakhruddin; Asha, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islam is a minority religion in Thailand. The Muslim population is concentrated in Southern Thailand. As a minority group, Muslims in Thailand especially in the southern region experience various social disparities. Education in Southern Thailand faces gaps and disparities that result in unequal development of Islamic education. This stands in contrast to Indonesia, where the majority of the population is Muslim. These historical and demographic differences have led to different approaches in how the Thai and Indonesian governments reconcile and develop Islamic education.